Analysis of Transparency Strategies and Challenges as a form of school accountability commitment: a literature study - Paryono; Riani, Lilia Pasca (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim : The purpose of this study was to evaluate different approaches to implementing transparency, which is a form of commitment to being for school management, and to discover the problems that arise when implementing it. Design/Methode/Approach : This research used the literature study method by reviewing various academic references, education policies and best practices in implementing transparency in schools. Data were collected and analyzed in three stages: data reduction, categorization, and interpretation. Research Finding : The results show that several key approaches can be used to achieve successful school transparency. These strategies include increasing stakeholder awareness and understanding, building an infrastructure that supports information disclosure, and implementing transparency gradually to reduce resistance. Theoretical contribution/Originality : This study enriches the existing body of knowledge by systematically evaluating various strategies for implementing transparency within school management. Unlike prior research that may have focused on singular approaches or lacked a comprehensive framework, this study synthesizes multiple methodologies, offering a holistic perspective on achieving transparency. Practitionel/Policy implication : In , to maintain sustainable transparency, schools should adopt a more accountable financial system, increase community participation in decision-making, and balance privacy and openness with applicable regulations. Schools can increase accountability, improve education governance and strengthen community relations by applying the right approach. Research limitation : The absence of empirical data means that the practical effectiveness of the proposed strategies remains to be validated in real-world settings.